Monetary policy shocks in a two-sector open economy: an empirical study - Ricardo Llaudes (European Central Bank (ECB), 2007)
This paper studies the effects and the transmission mechanism of unexpected monetary policy shocks in an open economy setting within the context of a VAR frame- work. It considers an economy with two sectors, a tradable sector and a non-tradable sector. For a given country, economic sectors are defined according to the proportion of output that is exported to other countries. This paper departs from the standard literature in that it tries to isolate the differential effects that monetary policy shocks may have on these two distinct sectors of the economy. The results show that the behavior of these two sectors varies whithin a country, with the tradable sector showing a higher degree of responsiveness to policy shocks than the non-tradable. This result is robust across the different countries in the sample and for a synthetic aggregate. The evidence presented gives an indication that industrial structure may be an important component for the analysis of monetary policy.
Keywords: C32; E52; F31; F42; 330; E52; F31; F42; Classification-JEL: C32; Monetary shock; small open economy; Structural VAR; Geldpolitik; Schock; Geldpolitische Transmission; Kleine offene Volkswirtschaft; VAR-Modell; Theorie